Diastolic blood pressure is an independent risk factor for periprocedural stroke following carotid endarterectomy in asymptomatic patients - Halliday, A; de Waard, D; de Borst, G; Bulbulia, R; Huibers, A (Elsevier, 2016)
Benefits of carotid endarterectomy (CEA) in stroke prevention partly depend on periprocedural risks. Although systolic hypertension is thought of as a risk factor for periprocedural events, effects of diastolic blood pressure (dBP) are often ignored. In a recent post-hoc analysis of ICSS, diastolic blood pressure was associated with adverse outcome after CEA in symptomatic patients. We aimed to identify whether this was also a risk factor for periprocedural stroke or death in asymptomatic patients in the Asymptomatic Carotid Surgery Trial (ACST-1).